Implikasi Yuridis Terhadap Anak di Luar Nikah dalam Persepektif Mazhab Syafi’i - Rio, Roma (JYRS: Journal of Youth Research and Studies, 2021)
Marriage is an inner and outer bond between a man and a woman as legal husband and wife based on the One Godhead. Marriage is an initial step to form a family, by requiring a partner who has integration in creating harmony in the family. Marriage causes a kinship relationship between children and their fathers so that they can have their rights. If the child is born out of wedlock, then the child does not get any rights against his father. This study uses a type of library research where the researcher examines written sources regarding nasab status and the implications of children out of wedlock according to the Syafi'i School. The researchers The researchers collected sources from existing library sources, sources derived from the translation of the book of the Shafi'i School, including Al-Umm (Imam Syafi'i), Mugniy al-Muhtaj (Muhammad bin al-Khatib asy-Syarbiniy), Syarh Sahih Muslim (An Nawawi), al-fiqh al-Islamiy wa Adillatuhu (Az-Zuhayliy). The results of this study are the lineage status of children out of wedlock according to the Syafi'i School that children out of wedlock are children born less than six months after intercourse with a legal husband, the lineage status of children out of wedlock with their biological father is blocked and disconnected. Then the child out of wedlock or the child of adultery has the status of a foreigner (Ajnabiyyah). The implication of a child out of wedlock is that there is no kinship relationship between the child and his biological father, so that the child is not burdened by his father in providing a living, there is no relationship between the two in terms of inheriting each other, and if the child out of wedlock is a woman, the child does not become his mahram. and not allowed to be alone between the two.